Effectiveness of eHealth interventions for the promotion of physical activity in older adults: a systematic review protocol. Issue 1 (December 2016) - Muellmann, Saskia; Forberger, Sarah; Möllers, Tobias; Zeeb, Hajo; Pischke, Claudia
Abstract Background It is known that regular physical activity (PA) is associated with improvements in physical, psychological, cognitive, and functional health outcomes. The World Health Organization recommends 150 min of moderate exercise per week for older adults to achieve these health benefits. However, only 20–60 % of adults aged 60 years and above currently meet these recommendations for exercise. The widespread use of the internet and mobile phones among older adults may open new opportunities to promote PA in this population. Findings of previous reviews suggest that eHealth interventions are effective in promoting PA in adults of various ages. However, to date, none of these reviews have provided a differentiated picture of engagement in such interventions and effects on PA among older adults. Also, we are unaware of any studies comparing effects of participation in eHealth vs. traditional paper-and-pencil interventions on PA in this population. The aim of this systematic review and meta-analysis is to compare the effectiveness of eHealth interventions promoting PA in older adults aged 55 years and above with either a non-eHealth PA intervention or a group that is not exposed to any intervention. Methods Eight electronic databases (MEDLINE, EMBASE, CINAHL, CENTRAL, PEI, PsycINFO, Web of Science, and OpenGrey) will be searched to identify experimental and quasi-experimental studies examining the effectiveness of eHealth interventions for PA promotion in adults aged 55 years and above. Two authors will independently select and review references, extract data, and assess the quality of the included studies by using the Cochrane Collaboration's risk of bias tool. Disagreements between authors will be resolved by discussion involving a third author. If feasible, a meta-analysis will be conducted. Narrative synthesis using harvest plots will be performed, should a meta-analysis not be feasible. Discussion The proposed systematic review will be the first review that compares the effectiveness of eHealth interventions promoting PA in older adults aged 55 years and above with control groups exposed to a non-eHealth intervention or to no intervention. The results of this review will provide new information regarding the question whether eHealth interventions are an effective intervention vehicle for PA promotion in this population. Systematic review registration PROSPEROCRD42015023875